(untitled) (Biological Sciences - PJSIR, 2022)
Mass culture of algae were prepared to feed poultry birds. Three species were selected as test algae which include one species of coccoid green algae (Chlorella vulgaris), one from filamentous green algae (Spirogyra ellipsospora) and a. thalloid marine green algae (Viva lactuca). Attempts were made to achieve a low cost feed with high nutritional potentia!. It was observed that the birds (chick broiler) feeding on coccoid and thalloid green algae showed best results in terms of yield and quality of meat.